The Eurasian species of Xyela (Hymenoptera, Xyelidae): taxonomy, host plants and distribution - Blank, Stephan M.; Shinohara, Akihiko; Altenhofer, Ewald (Zootaxa, 2013)
The 28 Eurasian species of Xyela Dalman, 1819 are revised based on material of ca 7,500 imagines including about 10 % reared specimens. Larvae of Eurasian Xyela usually are monophagous and feed inside the staminate cones of pines (Pinus spp., Pinaceae). Based on the reared material, on identification by barcoding and on additional collection observations, the larval host associations for the Xyela species are summarized and additional biological observations are noted. An illustrated key to the species and distribution maps are presented. Eight species are described as new: X. altenhoferi Blank, sp. nov. (Croatia), X. heldreichii Blank, sp. nov. (Albania, Greece), X. koraiensis Blank & Shinohara, sp. nov. (Russia, South Korea), X. peuce Blank, sp. nov. (Bulgaria), X. pumilae Blank & Shinohara, sp. nov. (Japan), X. rasnitsyni Blank & Shinohara, sp. nov. (China, Russia, South Korea), X. sibiricae Blank, sp. nov. (Mongolia, Russia), and X. uncinatae Blank, sp. nov. (Andorra, France, Spain, Switzerland). For the other species redescriptions are given. A lectotype is designated for X. longula Dalman, 1819, and neotypes are designated for X. graeca J.P.E.F. Stein, 1876 and Pinicola julii Brébisson, 1818. The following new synonymies are proposed: X. lii Xiao, 1988, syn. nov. of X. sinicola Maa, 1947; X. nigroabscondita Haris & Gyurkovics, 2011, syn. nov. of X. lugdunensis (Berland, 1943); and X. suwonae Ryu & Lee, 1992, syn. nov. of X. ussuriensis Rasnitsyn, 1965.